Health insurance and AIDS Drug Assistance Program (ADAP) increases retention in care among women living with HIV in the United States. Issue 8 (3rd August 2021) - Kay, Emma Sophia; Edmonds, Andrew; Ludema, Christina; Adimora, Adaora; Alcaide, Maria L.; Chandran, Aruna; Cohen, Mardge H.; Johnson, Mallory O.; Kassaye, Seble; Kempf, Mirjam-Colette; Moran, Caitlin A.; Sosanya, Oluwakemi; et al.
ABSTRACT: Our objective was to examine the association between healthcare payer type and missed HIV care visits among 1, 366 US women living with HIV (WLWH) enrolled in the prospective Women's Interagency HIV Study (WIHS). We collected secondary patient-level data (October 1, 2017-September 30, 2018) from WLWH at nine WIHS sites. We used bivariate and multivariable binary logistic regression to examine the relationship between healthcare payer type (cross-classification of patients' ADAP and health insurance enrollment) and missed visits-based retention in care, defined as no-show appointments for which patients did not reschedule. Our sample included all WLWH who self-reported having received HIV care at least once during the two consecutive biannual WIHS visits a year prior to October 1, 2017-September 30, 2018. In the bivariate model, compared to uninsured WLWH without ADAP, WLWH with private insurance + ADAP were more likely to be retained in care, as were WLWH with Medicaid only and private insurance only. In the adjusted model, WLWH with private insurance only were more likely to be retained in care compared to uninsured WLWH without ADAP. Private health insurance and ADAP are associated with increased odds of retention in care among WLWH.